Optimal Government Spending and Unemployment - Ludger Linnemann; Andreas Schabert (Tinbergen Institute, 2008)
We study optimal government spending in a business cycle model with frictional unemployment. The Ramsey optimal policy is contrasted with a reference policy which would be first best in a frictionless economy. Results are: the Ramsey policy i) implies a higher steady state ratio of government spending to private consumption than the reference policy; ii) is procyclical under technology shocks and countercyclical under demand shocks (while the public spending ratio to private consumption is always countercyclical); iii) stabilizes employment, in some cases even at the cost of higher consumption volatility; iv) is qualitatively unaltered in a sticky price version with jointly optimal monetary and fiscal policy.
Keywords: E62; E32; 330; Optimal fiscal policy; government spending; labor market frictions; unemployment; stabilization policy; Finanzpolitik; Öffentliche Ausgaben; Konjunktur; Friktionelle Arbeitslosigkeit; Wirtschaftliche Anpassung; Dynamisches Gleichgewicht; Wohlfahrtstheorie; Theorie